Spatial distribution of agricultural yields with elevated metal concentration of the island exposed to acid mine drainage - Delia B Senoro; Pauline B Bonifacio; Doreen R Mascareñas; Carlito B Tabelin; Froilan P Ney; Ma. Rowela L Lamac; Fibor J Tan (Brawijaya University, 2021)
An island province in the Philippines exposed to acid mine drainage for about 22-25 years, uncovered new discovery in selected agricultural yields. The acid mine drainage was from two open mine pits of higher elevation flowing to Boac and Mogpog River system. A total of 78 various agricultural yields samples with 234 specimens were collected and analyzed from six municipalities of Marinduque, Philippines in 2019. These agricultural yields were (A) vegetables, (B) root crops, (C) fruits, and (D) rice. Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES) Perkin Elmer Optima 8000 with ICP multi-element standard solution IV were used to detect metals concentration in the agricultural samples. Digestion of samples followed the EPA Method 200.3. Results were compared with the WHO/FAO limit followed by the identification of yields and areas that pose risks to public health. Determination of the spatial distribution was by ArcGIS. The six municipalities; i.e., Boac, Buenavista, Gasan, Mogpog, Torrijos and Sta. Cruz, were labelled as B, BV, G, M, T and S, respectively. Record showed that Sample A from G contain higher metal concentration among other yields. Manganese concentration in Samples A, B, and D were found to be higher than WHO/FAO limit. However, copper and zinc concentration in Sample C in all municipalities exceeded the allowable limit. Elevated total chromium concentration was found in Sample D collected from G, T, and S. These results would help relevant government agencies and units design strategies to mitigate the degraded agricultural lands and protect public health.